2016
DOI: 10.1111/tmi.12815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of response strategies against epidemics due to Neisseria meningitidis C in Niger

Abstract: Abstractobjective To inform public health recommendations, we evaluated the effectiveness and efficiency of current and hypothetical surveillance and vaccine response strategies against Neisseria meningitidis C meningitis epidemics in 2015 in Niger.methods We analysed reports of suspected and confirmed cases of meningitis from the region of Dosso during 2014 and 2015. Based on a definition of epidemic signals, the effectiveness and efficiency of surveillance and vaccine response strategies were evaluated by ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The limited number of LME did not allow serogroup-specific analysis, but a strong association between URTI and LME was seen during epidemic waves due to serogroup A and epidemics due to serogroups W or X. The recent epidemic wave due to a new meningococcal serogroup C strain in Nigeria and Niger 9 was constituted of localised epidemics that were spread across the epidemic regions without any systematic pattern 25 . In the light of the present findings, the epidemic emergence could be interpreted as a coincidence between the introduction of a new meningococcal strain and the occurrence of respiratory pathogen outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of LME did not allow serogroup-specific analysis, but a strong association between URTI and LME was seen during epidemic waves due to serogroup A and epidemics due to serogroups W or X. The recent epidemic wave due to a new meningococcal serogroup C strain in Nigeria and Niger 9 was constituted of localised epidemics that were spread across the epidemic regions without any systematic pattern 25 . In the light of the present findings, the epidemic emergence could be interpreted as a coincidence between the introduction of a new meningococcal strain and the occurrence of respiratory pathogen outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in the absence of a multivalent meningococcal vaccine preventive strategy, affected areas must rely on reactive immunization for outbreak control. However, as this epidemic illustrated, even with motivated staff and a well coordinated response, it may take months to detect, confirm, and mobilize vaccine for an effective reactive vaccination program [27], at which point the outbreak may be waning naturally. Implementation of an effective preventive meningococcal vaccination strategy, combined with continued adherence to strong surveillance with rapid laboratory confirmation to monitor disease trends, identify emerging epidemic strains, guide implementation, and evaluate program effectiveness, could minimize future reliance on reactive vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that the majority of districts were larger than 100 000 population, which is not consistent with WHO recommendations. Previous studies have demonstrated that surveillance at finer spatial scales may allow for more efficient and earlier use of vaccine where it is needed [7, 28].…”
Section: Discussionmentioning
confidence: 99%